Comparison of Resting PD/PA with Fractional Flow Reserve Using a Monorail Pressure Catheter - Koh, K.T.; Oon, Y.Y.; Khaw, C.S.; Mulia, E.; Voon, C.Y.; Said, A.; Cham, Y.L.; Shu, F.; Ho, K.H.; Tan, C.T.; Mohd Amin, N.H.; Khiew, N.Z.; et al. (Elsevier, 2017)
Background: The RXi™ system (ACIST Medical Systems, MN, USA) is a new Fractional Flow Reserve (FFR) technology utilising an ultrathinmonorail microcatheter (Navvus®; ACIST Medical Systems) with an optical pressure sensor located close to the distal catheter tip. FFR measurement using monorail microcatheter is comparable to the conventional pressure wires. However, the predictive value of resting distal coronary artery pressure/aortic pressure (Pd/Pa) on hyperemic FFR value in the real world practice is unknown. Objective: To explore the diagnostic accuracy of resting Pd/Pa in relation to hyperemic FFR using the monorail pressure catheter. Methods: Resting Pd/Pa and FFR were measured using monorail pressure catheter in 67 consecutive patients with intermediate coronary artery lesions (30% to 80% diameter stenoses) between 01-03-2016 to 17-01-2017. Of 121 studied lesions, 29 (23.97%) were excluded because of no hyperemic FFR due to postive resting Pd/Pa (n=17), severe or non-critical stenosis (n=11) and suboptimal acquisition (n=1), leaving 92 lesions for final analysis. Hyperemic FFR was induced with intracoronary adenosine. The selection of coronary wire and the dose of intracoronary nitroglycerine were at the operators’ discretions. Results: Bland-Altman plots showed a moderate degree of scatter between Pd/Pa and FFR value. On average, Pd/Pa exceeded FFR by 0.066 (-0.09 to +0.22). Receiver-operating characteristic curves of the resting Pd/Pa with FFR≤0.80 as the reference variable showed an area under the curve of 0.78 (95% confidence intervals 0.680 to 0.881, pb0.001), with a diagnostic accuracy of 79.3% when the resting Pd/Pa was ≤0.86. Certain cutoff values of Pd/Pa can reliably predict whether hyperemic FFR was positive or negative (FFR cutoff≤0.80). Resting Pd/Pa value of N0.96 had a negative predictive value (NPV) of 100% and sensitivity of 100%; the resting Pd/Pa value of ≤0.82 had a positive predictive value (PPV) of 100% and specificity of 98.3%. These were consistent regardless of coronary vessel, location of lesion or degree of diameter stenosis. Conclusions: Certain range of resting Pd/Pa measured by monorail pressure catheter had excellent NPV and sensitivity or excellent PPV and specificity to predict hyperemic FFR. Clinical outcome studies are required to determine whether the results might obviate the need for hyperemia in selected patients.